A nickel-manganese-aluminum hydroxide precursor for lithium-ion batteries and a preparation method thereof

By controlling the reaction conditions, the nickel-manganese aluminum hydroxide precursor is prepared and mixed with the lithium salt to calcinate to form a nickel-manganese aluminum oxide positive electrode material with a microsphere structure stacked by dense nanosheets, solving the problems of low tap density and poor synthesis consistency of the positive electrode material in the prior art, and achieving efficient lithium-ion battery performance and simplified process.

CN116514182BActive Publication Date: 2025-03-25EAST CHINA UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310562474.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-18
Publication Date
2025-03-25
Estimated Expiration
2043-05-18

AI Technical Summary

Technical Problem

The existing cobalt-free cathode materials lack the microsphere structure of dense nanosheet stacking, resulting in low tap density, poor synthesis consistency, low discharge specific capacity, poor charge and discharge performance and complex manufacturing processes.

Method used

By accurately controlling the pH value, stirring rate, ammonium complexing agent concentration and feed rate during the reaction process, a nickel manganese aluminum hydroxide precursor was prepared, and mixed with lithium salt to calcinate to obtain the nickel manganese aluminum oxide positive electrode material to form a densely packed microsphere structure.

Benefits of technology

It has achieved high tap density, excellent synthesis consistency, improved discharge specific capacity, excellent charge and discharge performance and simplified manufacturing processes, which is suitable for the commercial development of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116514182B_ABST
    Figure CN116514182B_ABST
Patent Text Reader

Abstract

The present invention discloses a nickel-manganese-aluminum hydroxide precursor for lithium-ion batteries and a preparation method thereof. The preparation method is carried out by adding nickel salt, manganese salt, aluminum oxalate chelate, hydroxide and ammonium compound into a base liquid for coprecipitation reaction to obtain a mixture; wherein the base liquid is ammonia water; the aluminum oxalate chelate is obtained by mixing aluminum salt and oxalate; and then the mixture is subjected to an aging reaction to obtain a nickel-manganese-aluminum hydroxide precursor. Ultra-uniform dispersion of aluminum is achieved by precise control of key parameters in the coprecipitation process. The nickel-manganese-aluminum hydroxide precursor prepared by the method is a microsphere structure composed of densely packed nanosheets, the volume average particle size of the microspheres is 7-15μm, and the tap density can reach 1.5-2.5g / cm 3 The nickel-manganese-aluminum oxide cathode material prepared from the precursor greatly inhibits the mixing of lithium and nickel, and its application in lithium-ion batteries achieves excellent rate charge and discharge capabilities and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium batteries, and in particular to a nickel-manganese-aluminum hydroxide precursor for lithium-ion batteries and a preparation method thereof. Background Art

[0002] The electrification of automobiles through electrochemical energy storage can reduce the proportion of non-renewable energy such as fossil resources in the existing energy structure, reduce environmental pollution and optimize the energy structure. Lithium-ion batteries have the advantages of high energy density, good cycle stability, and no obvious memory effect, making them the preferred power source for new energy vehicles at this stage. However, the low specific capacity and high price of cathode materials limit their further commercial development.

[0003] For mainstream layered oxide positive electrode materials, increasing the nickel content and reducing the cobalt content are the main ways to achieve high specific capacity and reduce prices. However, with the increase in nickel content, the increase in the content of divalent nickel in the positive electrode material will lead to serious lithium-nickel mixing. Although the cobalt element can balance the charge and enhance the conductivity, thereby alleviating the lithium-nickel mixing phenomenon and improving the rate charge and discharge performance of the material. However, due to the small amount of cobalt raw materials, the price is relatively expensive, and the toxicity of cobalt during its mining process will also cause serious health and ethical problems. Therefore, in the synthesis process of ternary positive electrode materials, reducing the use of cobalt is the focus of the current development of lithium-ion batteries. However, the prior art does not disclose a method for continuously and stably preparing high-nickel cobalt-free layered oxide positive electrode materials.

[0004] Patent CN109686970A discloses a method for synthesizing a cobalt-free lithium-rich ternary positive electrode material, which uses cheap manganese to replace expensive cobalt, and introduces excess lithium to composite the layered LiNiO2 phase with the layered LiMnO2 phase to prepare a lithium-rich layered nickel-manganese-aluminum positive electrode material. The positive electrode material has a specific capacity of 190mAh / g at 0.1C, and a capacity retention rate of more than 90% after 100 cycles.

[0005] Patent CN113809294A discloses a method for synthesizing a cobalt-free high-nickel cathode material, which uses iron ions to replace cobalt to synthesize LiNi x Fe y Mn (1-x-y) O2 positive electrode material. The obtained nanomaterial has good electrochemical behavior and significantly reduces the cost of material synthesis.

[0006] Although the above methods synthesize high-nickel cobalt-free oxide positive electrode materials and reduce the cost of raw materials, the above materials do not have a microsphere structure with dense nanosheet stacking, resulting in a low tap density, and there are problems such as poor synthesis consistency, low discharge specific capacity, poor charge and discharge performance, and complex manufacturing process, which makes it difficult to meet the needs of the commercial development of lithium-ion batteries. Among them, the microsphere structure with dense nanosheet stacking refers to a microsphere structure with excellent sphericity, uniform volume average particle size, and densely stacked primary particles. Therefore, it is urgent to develop a high-nickel cobalt-free layered oxide positive electrode material with high tap density, excellent synthesis consistency, high discharge specific capacity, excellent charge and discharge performance, and simple process. Summary of the invention

[0007] The technical problem to be solved by the present invention is to overcome the problems in the prior art that the cobalt-free oxide positive electrode material has no microsphere structure, resulting in a low tap density, and there are problems such as poor synthesis consistency, low discharge specific capacity, poor charge and discharge performance, and complex manufacturing process, and provide a nickel manganese aluminum hydroxide precursor for lithium ion batteries and a preparation method thereof. The preparation method of the nickel manganese aluminum hydroxide precursor provided by the present invention can ensure that the prepared nickel manganese aluminum hydroxide precursor and the nickel manganese aluminum oxide positive electrode material obtained by mixing and calcining the precursor with a lithium salt form a densely packed microsphere structure, with high tap density, excellent synthesis consistency, and simple process, and it is applied to lithium ion batteries to exhibit excellent rate charge and discharge capabilities and cycle life.

[0008] The present invention solves the above technical problems through the following technical solutions.

[0009] The present invention also provides a method for preparing a nickel-manganese-aluminum hydroxide precursor, which comprises the following steps:

[0010] (1) adding nickel salt, manganese salt, aluminum oxalate chelate, hydroxide and ammonium compound to a base liquid for coprecipitation reaction to obtain a mixture; wherein the base liquid is ammonia water; and the aluminum oxalate chelate is obtained by mixing aluminum salt and oxalate;

[0011] (2) The mixture of step (1) is subjected to an aging reaction to obtain a nickel-manganese-aluminum hydroxide precursor.

[0012] In step (1), the nickel salt may be a conventional nickel salt in the art, preferably one or more of nickel sulfate, nitrate, acetate and chloride, more preferably nickel sulfate, for example, nickel sulfate hexahydrate.

[0013] In step (1), the manganese salt may be a conventional manganese salt in the art, preferably one or more of manganese sulfate, nitrate, acetate and chloride, more preferably manganese sulfate, for example, manganese sulfate monohydrate.

[0014] In a preferred embodiment of the present invention, the molar ratio of the nickel salt to the manganese salt is preferably (18-19):1, for example 18:1.

[0015] In a preferred embodiment of the present invention, the nickel salt and the manganese salt are preferably used in the form of a nickel-manganese salt solution.

[0016] In a preferred embodiment of the present invention, the nickel-manganese salt solution is preferably obtained by mixing the nickel salt, the manganese salt and a solvent, wherein the solvent is preferably water.

[0017] In a preferred embodiment of the present invention, the concentration of the nickel manganese salt solution is preferably 1.5-2.5 mol / L, such as 2 mol / L.

[0018] In a preferred embodiment of the present invention, the aluminum salt may be a conventional aluminum salt in the art, preferably an aluminum sulfate, for example, aluminum sulfate.

[0019] In a preferred embodiment of the present invention, the oxalate may be a conventional oxalate in the art, preferably sodium oxalate or ammonium oxalate, more preferably sodium oxalate.

[0020] In a preferred embodiment of the present invention, the molar ratio of aluminum salt to oxalate is preferably (2-5):1, for example 3:1.

[0021] In a preferred embodiment of the present invention, the molar ratio of the aluminum salt to the manganese salt is preferably (0.1-1):1, for example 1:1.

[0022] In step (1), the aluminum oxalate chelate is preferably used in the form of an aluminum oxalate chelate solution.

[0023] In a preferred embodiment of the present invention, the aluminum oxalate chelate solution is preferably obtained by mixing the aluminum salt, the oxalate and a solvent, wherein the solvent is preferably water.

[0024] In a preferred embodiment of the present invention, the concentration of the aluminum oxalate chelate solution is preferably 0.1-0.3 mol / L, such as 0.2 mol / L.

[0025] In step (1), the hydroxide may be a conventional hydroxide in the art, preferably sodium hydroxide and / or potassium hydroxide, more preferably sodium hydroxide.

[0026] In a preferred embodiment of the present invention, the molar ratio of hydroxide to manganese salt is preferably (36-44):1, for example 40:1.

[0027] In a preferred embodiment of the present invention, the hydroxide is preferably used in the form of a hydroxide solution.

[0028] In a preferred embodiment of the present invention, the hydroxide solution is preferably obtained by mixing the hydroxide and a solvent, wherein the solvent is preferably water.

[0029] In a preferred embodiment of the present invention, the concentration of the hydroxide solution is preferably 3-5 mol / L, such as 4 mol / L or 5 mol / L.

[0030] In step (1), the ammonium compound may be a conventional ammonium compound in the art, preferably ammonia water and / or an ammonium salt, more preferably ammonia water. The ammonium salt is preferably one or more of ammonium nitrate, ammonium sulfate, ammonium acetate, ammonium chloride and ammonium bicarbonate.

[0031] In a preferred embodiment of the present invention, the molar ratio of the ammonium compound to the manganese salt is preferably (27-36):1, such as 27:1 or 36:1.

[0032] In a preferred embodiment of the present invention, the ammonium compound is preferably used in the form of an ammonium compound solution.

[0033] In a preferred embodiment of the present invention, the ammonium compound solution is preferably obtained by mixing the ammonium compound and a solvent, wherein the solvent is preferably water.

[0034] In a preferred embodiment of the present invention, the concentration of the ammonium compound solution is preferably 2.4-4.5 mol / L, such as 3.6 mol / L or 4.5 mol / L. The present invention ensures the formation of a densely packed microsphere structure by controlling the concentration of the ammonium compound solution.

[0035] In step (1), the base liquid is preferably pretreated before the coprecipitation reaction.

[0036] In a preferred embodiment of the present invention, the concentration of the base solution is 1 / 3 of the concentration of the ammonium compound solution, preferably 0.8-1.5 mol / L, such as 0.8 mol / L or 1.2 mol / L.

[0037] In a preferred embodiment of the present invention, the stirring speed of the pretreatment is preferably 600-800 rpm, such as 600 rpm or 800 rpm.

[0038] In a preferred embodiment of the present invention, the reaction temperature of the pretreatment is preferably 50-61°C, such as 50°C or 55°C.

[0039] In a preferred embodiment of the present invention, the pretreatment process may also preferably include introducing a protective gas.

[0040] In a preferred embodiment of the present invention, the protective gas is preferably an inert atmosphere, such as argon or nitrogen.

[0041] In a preferred embodiment of the present invention, the flow rate of the protective gas is preferably 50-100 mL / min, such as 50 mL / min or 100 mL / min.

[0042] In step (1), the stirring speed of the coprecipitation reaction is preferably 600-800 rpm, such as 600 rpm or 800 rpm.

[0043] In a preferred embodiment of the present invention, the reaction temperature of the coprecipitation reaction is preferably 50-61°C, such as 50°C or 55°C.

[0044] In a preferred embodiment of the present invention, the coprecipitation reaction may also preferably include introducing a protective gas.

[0045] In a preferred embodiment of the present invention, the protective gas is preferably an inert atmosphere, such as argon or nitrogen.

[0046] In a preferred embodiment of the present invention, the flow rate of the protective gas is preferably 50-100 mL / min, such as 50 mL / min or 100 mL / min.

[0047] In step (1), the coprecipitation reaction can be carried out in any reaction container, and the reaction container is preferably a reactor.

[0048] In a preferred embodiment of the present invention, during the coprecipitation reaction, the pH value in the reaction container is preferably 10.8-11.2, such as 11.0 or 11.2. The present invention ensures the formation of a densely packed microsphere structure by controlling the pH value in the reaction container.

[0049] In a preferred embodiment of the present invention, the total amount of the mixture added is preferably 2 / 3 of the volume of the reaction container.

[0050] In a preferred embodiment of the present invention, the nickel manganese salt solution, the aluminum oxalate chelate solution, the hydroxide solution and the ammonium compound solution preferably enter the reaction container through a peristaltic pump at different flow rates.

[0051] In a preferred embodiment of the present invention, the nickel manganese salt solution, the hydroxide solution and the ammonium compound solution are preferably added to the reaction container at a first flow rate, preferably 0.5-0.8 mL / min, such as 0.5 mL / min; and the aluminum oxalate chelate solution is preferably added to the reaction container at a second flow rate, preferably 0.25-0.4 mL / min, such as 0.25 mL / min. The present invention ensures the formation of a densely packed microsphere structure by controlling the first flow rate and the second flow rate.

[0052] In step (2), the aging reaction can be carried out in any reaction container, and the reaction container is preferably a reactor.

[0053] In a preferred embodiment of the present invention, the aging reaction time is preferably 10-20 hours, such as 10 hours or 20 hours.

[0054] In a preferred embodiment of the present invention, after the aging reaction is completed, it is also preferably included in the operation of "washing, drying" and / or iron removal;

[0055] In a preferred embodiment of the present invention, after the aging reaction, washing, drying and iron removal operations are preferably included in sequence.

[0056] The present invention provides a nickel manganese aluminum hydroxide precursor prepared by the above preparation method, wherein the molecular formula of the nickel manganese aluminum hydroxide precursor is Ni 1-x-y Mn x Al y (OH)2, where 0<x≤0.05, 0<y≤0.05.

[0057] In a preferred embodiment of the present invention, the molecular formula of the nickel manganese aluminum hydroxide precursor is preferably Ni 0.90 Mn 0.05 Al 0.05 (OH)2.

[0058] In a preferred embodiment of the present invention, the nickel manganese aluminum hydroxide precursor is a microsphere structure composed of densely packed nanosheets.

[0059] In a preferred embodiment of the present invention, the volume average particle size of the microspheres is preferably 7-15 μm; more preferably 8-13 μm, such as 8 μm, 10 μm, 11 μm or 13 μm.

[0060] The volume average particle size of the microspheres is the volume of one microsphere with this diameter, which is exactly equal to the volume average of all microspheres.

[0061] In a preferred embodiment of the present invention, the specific surface area of ​​the microspheres is 3.0-7.5 m 2 / g, for example 4.5m 2 / g or 6.2m 2 / g.

[0062] The specific surface area of ​​the microspheres is the total surface area per unit mass of the microspheres.

[0063] In a preferred embodiment of the present invention, the tap density of the microspheres is 1.5-2.5 g / cm 3 , for example 2.1 g / cm 3 .

[0064] The tap density of the microspheres is the mass per unit volume of the microspheres in the container after being tapped under specified conditions.

[0065] In a preferred embodiment of the present invention, the thickness of the nanosheet is preferably 15-50 nm, for example 30 nm.

[0066] In a preferred embodiment of the present invention, the width of the nanosheet is preferably 100-500 nm, for example 300 nm.

[0067] In a preferred embodiment of the present invention, the length of the nanosheet is preferably 100-500 nm, such as 300 nm.

[0068] The present invention also provides a nickel-manganese-aluminum oxide positive electrode material, comprising the nickel-manganese-aluminum hydroxide precursor and a lithium salt, and the chemical formula thereof is LiNi 1-x-y Mn x Al y O2.

[0069] In a preferred embodiment of the present invention, 1-xy is preferably 0-0.8, x is preferably 0-0.1, and y is preferably 0-0.1.

[0070] The present invention also provides a method for preparing a nickel-manganese-aluminum oxide positive electrode material, which comprises the following steps: mixing a nickel-manganese-aluminum hydroxide precursor with a lithium salt and sintering them.

[0071] In a preferred embodiment of the present invention, the sintering is preferably a two-stage sintering, which consists of a first stage sintering and a second stage sintering.

[0072] In a preferred embodiment of the present invention, the heating rate of the two-stage sintering is preferably 2-5°C / min.

[0073] In a preferred embodiment of the present invention, the sintering temperature of the first stage sintering is preferably 400-600° C., and the sintering time is preferably 4-6 hours.

[0074] In a preferred embodiment of the present invention, the sintering temperature of the second sintering stage is preferably 700-800° C., and the sintering time is preferably 12-18 hours.

[0075] The present invention also provides an application of the nickel-manganese-aluminum oxide positive electrode material in a lithium-ion battery.

[0076] In the present invention, the operation of preparing the nickel manganese aluminum oxide positive electrode material can be a conventional operation in the art, preferably, it is prepared by mixing and sintering the above-mentioned nickel manganese aluminum hydroxide precursor and lithium salt.

[0077] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0078] The reagents and raw materials used in the present invention are commercially available.

[0079] The technical principle of the present invention is: a soluble nickel manganese salt solution, an aluminum oxalate chelate solution, a hydroxide solution and an ammonium compound solution are pumped into a sealed reactor containing a certain concentration of ammonia bottom liquid under the protection of an inert atmosphere at a certain flow rate to carry out a mixed reaction, and the crystal nucleus formation and crystal growth process are regulated by controlling the pH value, stirring rate, bottom liquid concentration and different feed rates in the reactor. Process parameters such as the preparation of a nickel manganese aluminum hydroxide precursor with a microsphere structure of densely packed nanosheets. The obtained precursor is mixed with a lithium salt and calcined to obtain a nickel manganese aluminum oxide positive electrode material. The nickel manganese aluminum oxide positive electrode material with a microsphere structure has a dense microsphere structure, and its application in lithium ion batteries exhibits excellent rate charge and discharge capabilities and cycle performance, as well as a simple process and excellent synthesis consistency.

[0080] The positive and progressive effects of the present invention are:

[0081] 1. The nickel-manganese-aluminum hydroxide precursor prepared by the preparation method of the present invention has a microsphere structure of densely packed nanosheets, the average volume particle size of the microsphere is 7-15 μm, and the tap density can reach 1.5-2.5 g / cm 3 .

[0082] 2. The nickel manganese aluminum oxide positive electrode material containing the nickel manganese aluminum hydroxide precursor prepared by the preparation method of the present invention is applied to lithium ion batteries, showing excellent rate charge and discharge capability and cycle performance, and can achieve a specific capacity of ≥135 mAh / g at a current density of 10C and a capacity retention rate of ≥95.9% after 100r of cycling at 1C.

[0083] 3. The preparation method provided by the present invention can realize continuous preparation, has a simple process, and is suitable for industrial large-scale production.

[0084] 4. The preparation method provided by the present invention has controllable preparation process parameters and the obtained microsphere structure of nanosheet stacking is repeatable, so the synthesis consistency is excellent. BRIEF DESCRIPTION OF THE DRAWINGS

[0085] Figure 1 This is a low-magnification SEM image of the nickel-manganese-aluminum hydroxide precursor 1K prepared in Example 1.

[0086] Figure 2 This is a low-magnification SEM image of the nickel-manganese-aluminum hydroxide precursor 5K prepared in Example 1.

[0087] Figure 3 This is a low-magnification SEM image of the nickel-manganese-aluminum hydroxide precursor 20K prepared in Example 1.

[0088] Figure 4 This is the particle size distribution diagram of the nickel manganese aluminum hydroxide precursor prepared in Example 1.

[0089] Figure 5 This is a low-magnification SEM image of the nickel-manganese-aluminum hydroxide precursor 1K prepared in Comparative Example 1.

[0090] Figure 6 This is a low-magnification SEM image of the oxide 5K synthesized after the nickel-manganese-aluminum hydroxide precursor prepared in Example 1 was intercalated with lithium and calcined.

[0091] Figure 7 This is a low-magnification SEM image of the oxide 20K synthesized after the nickel-manganese-aluminum hydroxide precursor prepared in Example 1 was intercalated with lithium and calcined.

[0092] Figure 8 This is the XRD pattern of the oxide synthesized after the nickel manganese aluminum hydroxide precursor prepared in Example 1 was intercalated with lithium and calcined.

[0093] Fig. 9 This is a graph of the rate charge and discharge performance of a lithium-ion battery assembled from the oxide synthesized after lithium insertion and calcination of the nickel-manganese-aluminum hydroxide precursor prepared in Example 1.

[0094] Fig.10 This is a long cycle performance diagram of a lithium-ion battery assembled from the oxide synthesized after lithium insertion and calcination of the nickel-manganese-aluminum hydroxide precursor prepared in Example 1.

[0095] Fig.11 This is a rate charge and discharge performance diagram of a lithium-ion battery assembled from an oxide synthesized after lithium insertion and calcination of the nickel-manganese-aluminum hydroxide precursor prepared in Example 1.

[0096] Fig.12 This is a long cycle performance diagram of a lithium-ion battery assembled from an oxide synthesized after lithium insertion and calcination of the nickel-manganese-aluminum hydroxide precursor prepared in Example 1. DETAILED DESCRIPTION

[0097] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0098] The raw materials in the embodiments of the present invention can all be commercially available products, and the kettle equipment is a conventional ternary precursor co-precipitation kettle.

[0099] Example 1

[0100] Prepare 1600 mL of 1.2 mol / L ammonia solution as the base liquid, add the above solution into the reactor, start stirring at a speed of 800 rpm, and heat the reactor with circulating water at a heating temperature of 55°C. At the same time, introduce argon protective gas at a gas flow rate of 50 mL / min.

[0101] Prepare 600 mL of 2 mol / L nickel manganese sulfate solution: mix 1.08 mol of nickel sulfate hexahydrate, 0.06 mol of manganese sulfate monohydrate and solvent water.

[0102] Prepare 300 mL of 0.2 mol / L aluminum oxalate chelate solution: Mix 0.06 mol aluminum sulfate, 0.18 mol sodium oxalate and solvent water (wherein, the Al in sodium oxalate and aluminum sulfate in the prepared aluminum oxalate chelate solution is 0.18 mol / L). 3+ The molar ratio is 3:1).

[0103] Prepare 600mL of 4mol / L sodium hydroxide solution: Mix 2.4mol of sodium hydroxide with solvent water.

[0104] Prepare 600 mL of 3.6 mol / L ammonia solution: Mix 2.16 mol of concentrated ammonia solution with an initial concentration of 13.33 mol / L with solvent water.

[0105] The prepared nickel manganese sulfate solution, sodium hydroxide solution, and ammonia solution were pumped into the reactor with the bottom liquid at a flow rate of 0.5 mL / min and the aluminum oxalate chelate solution was pumped into the reactor with the bottom liquid at a flow rate of 0.25 mL / min by a peristaltic pump for coprecipitation reaction. During the reaction, the pH value was controlled to be about 11.0, the bottom liquid ammonia concentration was 1.2 mol / L, the stirring speed was 800 rpm, the argon protective gas flow rate was 50 mL / min, the reaction temperature was 55 ° C, and the feeding time was 20 hours. When the reactor material was close to 2 / 3 of the reactor volume, the feeding was stopped (the reactor material had been fully added), and the aging reaction was started. After aging for 10 hours, the suspension in the reactor was washed, dried, and iron-removed to obtain a nickel manganese aluminum hydroxide precursor, whose molecular formula is Ni 0.9 Mn0.05 Al 0.05 (OH)2, volume average particle size is 10.05 μm, specific surface area is 4.5 m 2 / g, tap density is 2.1g / cm 3 .

[0106] Example 2

[0107] Prepare 1600 mL of 0.9 mol / L ammonia solution as the base liquid, add the solution into the reactor, start stirring at 600 rpm, and heat the reactor with circulating water at 60°C. At the same time, introduce argon protective gas at a gas flow rate of 100 mL / min.

[0108] The nickel manganese sulfate solution, aluminum oxalate chelate solution and sodium hydroxide solution were prepared in the same manner as in Example 1.

[0109] Prepare 600mL of 2.7mol / L ammonia solution: Mix 1.62mol ammonia solution with solvent water.

[0110] The prepared nickel manganese sulfate solution, sodium hydroxide solution, and ammonia solution were pumped into the reactor with the bottom liquid at a flow rate of 0.5 mL / min by a peristaltic pump, and the aluminum oxalate chelate solution was pumped into the reactor with the bottom liquid at a flow rate of 0.25 mL / min for co-precipitation reaction. During the reaction process, the pH value was controlled to be fixed at 11.2, the ammonia concentration of the bottom liquid was 0.9 mol / L, the stirring speed was 600 rpm, the argon protective gas flow rate was 100 mL / min, the reaction temperature was 60°C, and the feeding time was 20 hours. When the reactor material was close to 2 / 3 of the reactor volume, the feeding was stopped and the aging reaction was started. After aging for 10 hours, the suspension in the reactor was washed, dried, and iron removed to obtain a nickel manganese aluminum hydroxide precursor, whose molecular formula is Ni 0.9 Mn 0.05 Al 0.05 (OH)2, volume average particle size is 8.5 μm, specific surface area is 6.2 m 2 / g, tap density is 1.9g / cm 3 .

[0111] Comparative Example 1

[0112] Prepare 1600 mL of 1 mol / L ammonia solution as the base liquid, add the solution into the reactor, start stirring at 800 rpm, and heat the reactor with circulating water at 55°C. At the same time, introduce argon protective gas at a gas flow rate of 50 mL / min.

[0113] The nickel manganese sulfate solution, aluminum oxalate chelate solution and sodium hydroxide solution were prepared in the same manner as in Example 1.

[0114] Prepare 600mL of 3mol / L ammonia solution: mix 1.8mol of ammonia solution with solvent water.

[0115] The prepared nickel manganese sulfate solution, sodium hydroxide solution, and ammonia solution were pumped into the reactor with the bottom liquid at a flow rate of 0.5 mL / min and the aluminum oxalate chelate solution was pumped into the reactor with the bottom liquid at a flow rate of 0.25 mL / min by a peristaltic pump for co-precipitation reaction. During the reaction, the pH value was controlled to be fixed at 11.8, the ammonia concentration of the bottom liquid was 1 mol / L, the stirring speed was 800 rpm, the argon protective gas flow rate was 50 mL / min, the reaction temperature was 55 ° C, and the feeding time was 20 hours. When the reactor material was close to 2 / 3 of the reactor volume, the feeding was stopped and the aging reaction was started. After aging for 20 hours, the suspension in the reactor was washed, dried, and iron-removed to obtain a nickel manganese aluminum hydroxide precursor, whose molecular formula is Ni 0.9 Mn 0.05 Al 0.05 (OH)2, with a volume average particle size of 5.2 μm and poor sphericity, results in poor electrochemical performance.

[0116] Effect Example 1 Morphology Characterization

[0117] Scanning electron microscope (SEM) test: Instrument model: S-4800, Hitachi, Japan. The morphology of the nickel-manganese-aluminum hydroxide precursor in Examples 1-2 and Comparative Example 1 and the oxide synthesized after the nickel-manganese-aluminum hydroxide precursor was intercalated with lithium and calcined was characterized by SEM.

[0118] Figure 1 This is a low-magnification SEM image of the nickel-cobalt-manganese hydroxide precursor 1K prepared in Example 1. It can be seen that the volume average particle size of the formed microspheres is relatively uniform, indicating that the synthesized material has good consistency.

[0119] Figure 2 This is a low-magnification SEM image of the nickel-cobalt-manganese hydroxide precursor 5K prepared in Example 1. It can be seen that the material is a secondary sphere with a volume average particle size greater than 10 μm formed by dense accumulation of nanosheets.

[0120] Figure 3 This is a low-magnification SEM image of the nickel-cobalt-manganese hydroxide precursor 20K prepared in Example 1, which magnifies the microsphere structure. It can be seen that the nanosheets are small and thin, compactly stacked, and the surface of the precursor is smooth and dense.

[0121] Figure 4 This is a particle size distribution diagram of the nickel-cobalt-manganese hydroxide precursor prepared in Example 1. It can be seen that it is a microsphere structure composed of uniform and densely packed nanosheets, and the volume average particle size of the microsphere is 7-15 μm.

[0122] Figure 5 This is a low-magnification SEM image of the nickel-manganese-aluminum hydroxide precursor 1K prepared in Comparative Example 1, which has poor sphericity and a volume average particle size of only about 5 μm.

[0123] Figure 6 This is a low-magnification SEM image of the oxide 5K synthesized after the nickel-manganese-aluminum hydroxide precursor prepared in Example 1 was intercalated with lithium and calcined. Figure 7 This is a low-magnification SEM image of the oxide 20K synthesized after the lithium-intercalated calcination of the nickel-manganese-aluminum hydroxide precursor obtained in Example 1. The finished secondary spheres formed after calcination have good sphericity, a volume average particle size of about 10 μm, and the primary particles are densely packed in blocks of equal size in all directions.

[0124] Effect Example 2 Structural Characterization

[0125] X-ray diffraction (XRD) test: Instrument model: Rigaku D / Max 2550, Rigaku Corporation, Japan.

[0126] The morphologies of the nickel manganese aluminum hydroxide precursor prepared in Example 1 and the oxide synthesized after lithium insertion and calcination of the nickel manganese aluminum hydroxide precursor were characterized by SEM.

[0127] Figure 8 This is the XRD pattern of the oxide synthesized after the nickel manganese aluminum hydroxide precursor was intercalated with lithium and calcined in Example 1. It proves that the prepared material is a single-phase nickel manganese aluminum oxide with extremely low lithium-nickel mixing.

[0128] Effect Example 3 Electrochemical Performance Test

[0129] Cycle and rate performance test: Instrument model: LANDCT 2001A battery test system

[0130] Assembly and testing of 2016 button half-cell: The nickel manganese aluminum hydroxide precursor material prepared in Example 1-2 and Comparative Example 1 was uniformly mixed with a lithium salt in a molar ratio of 1:1.05, wherein the lithium salt was lithium hydroxide. The mixture was kept at 500°C for 5 hours and at 750°C for 15 hours in a tube furnace, the atmosphere was a pure oxygen environment, the oxygen flow rate was 300 mL / min, and the heating rate during the sintering process was 5°C / min. The obtained nickel manganese aluminum oxide positive electrode material, namely the nickel manganese aluminum oxide positive electrode material, had a molecular formula of LiNi 0.9 Mn 0.05 Al 0.05 O2.

[0131] The nickel manganese aluminum oxide positive electrode material, the conductive agent Super P, and the binder polyvinylidene fluoride prepared in the above Example 1 and Comparative Example 1 were uniformly mixed in an appropriate amount of N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, and stirred uniformly for more than 4 hours under dry and sealed conditions. Then, the slurry was coated on aluminum foil and dried at 120°C for 12 hours under a vacuum environment to obtain a positive electrode. The loading amount of the positive electrode material was 1-2 g / cm 2 A 2016-type button half-cell was assembled in an argon-filled glove box, using a lithium sheet as the counter electrode, a polypropylene film (Celgard-2400) as the separator, and an electrolyte of 1.2 M LiPF6 dissolved in a solvent containing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:7, with 2% VC added.

[0132] The performance of the lithium-ion battery containing the nickel-manganese-aluminum ternary positive electrode material of the present invention prepared in the above steps was tested in a constant current charge and discharge mode in a blue electric test system LANDCT2001A (1C=180mAh / g).

[0133] Fig. 9 This is a graph of the rate charge and discharge performance of a lithium-ion battery assembled from the oxide synthesized after lithium insertion and calcination of the nickel-manganese-aluminum hydroxide precursor prepared in Example 1.

[0134] Fig.10 This is a long cycle performance diagram of a lithium-ion battery assembled from the oxide synthesized after lithium insertion and calcination of the nickel-manganese-aluminum hydroxide precursor prepared in Example 1.

[0135] Fig.11 This is a rate charge and discharge performance diagram of a lithium-ion battery assembled from an oxide synthesized after lithium insertion and calcination of the nickel-manganese-aluminum hydroxide precursor prepared in Example 1.

[0136] Fig.12 This is a long cycle performance diagram of a lithium-ion battery assembled from an oxide synthesized after lithium insertion and calcination of the nickel-manganese-aluminum hydroxide precursor prepared in Example 1.

[0137] Figure 9-11 The test results are shown in Table 1 below:

[0138] Table 1 Performance parameters of lithium ion batteries of Example 1 and Comparative Example 1

[0139]

[0140] As can be seen from Table 1, the lithium-ion battery prepared by using the oxide synthesized after lithium-intercalation calcination of the nickel-manganese-aluminum hydroxide precursor prepared in Example 1 has a higher specific capacity at 10C and a capacity retention rate after 100 cycles than those in Comparative Example 1. It achieves a specific capacity of up to 136 mAh / g at a current density of 10C, and still has an ultra-high capacity retention rate of 95.9% after cycling for 100 cycles at a current density of 1C.

Claims

1. A method for preparing a nickel-manganese-aluminum hydroxide precursor, characterized in that: It includes the following steps: (1) adding nickel salt, manganese salt, aluminum oxalate chelate, hydroxide and ammonium compound to a base liquid for coprecipitation reaction to obtain a mixture; wherein the base liquid is ammonia water; and the aluminum oxalate chelate is obtained by mixing aluminum salt and oxalate; (2) subjecting the mixture of step (1) to an aging reaction to obtain a nickel-manganese-aluminum hydroxide precursor; In step (1), the nickel salt is one or more of nickel sulfate, nitrate, acetate and chloride; In step (1), the manganese salt is one or more of manganese sulfate, nitrate, acetate and chloride; In step (1), the molar ratio of the nickel salt to the manganese salt is (18-19):1; In step (1), the nickel salt and the manganese salt are used in the form of a nickel-manganese salt solution; the concentration of the nickel-manganese salt solution is 1.5-2.5 mol / L; In step (1), the aluminum salt is aluminum sulfate; In step (1), the oxalate is sodium oxalate or ammonium oxalate; In step (1), the molar ratio of the aluminum salt to the oxalate is (2-5):1; In step (1), the molar ratio of the aluminum salt to the manganese salt is (0.1-1):1; In step (1), the aluminum oxalate chelate is used in the form of an aluminum oxalate chelate solution; the concentration of the aluminum oxalate chelate solution is 0.1-0.3 mol / L; In step (1), the hydroxide is sodium hydroxide and / or potassium hydroxide, and the hydroxide is used in the form of a hydroxide solution; the concentration of the hydroxide solution is 3-5 mol / L; In step (1), the molar ratio of the hydroxide to the manganese salt is (36-44):1; In step (1), the ammonium compound is ammonia water and / or ammonium salt, and the ammonium compound is used in the form of an ammonium compound solution; the concentration of the ammonium compound solution is 2.4-4.5 mol / L; In step (1), the molar ratio of the ammonium compound to the manganese salt is (27-36):1; In step (1), the base liquid is pretreated before the coprecipitation reaction; In step (1), the stirring speed of the coprecipitation reaction is 600-800 rpm; In step (1), the reaction temperature of the coprecipitation reaction is 50-61°C; In step (1), during the coprecipitation reaction, a protective gas is introduced, wherein the protective gas is an inert atmosphere and the flow rate of the protective gas is 50-100 mL / min; In step (2), the aging reaction time is 10-20 h; The concentration of the base solution is 1 / 3 of the concentration of the ammonium compound solution; The stirring speed of the pretreatment is 600-800 rpm; The reaction temperature of the pretreatment is 50-61°C; The pretreatment process also includes introducing a protective gas, wherein the protective gas is an inert atmosphere; During the coprecipitation reaction, the pH value in the reaction container is 10.8-11.2; The nickel manganese salt solution, the hydroxide solution and the ammonium compound solution are added to the reaction vessel at a first flow rate, wherein the first flow rate is 0.5-0.8 mL / min; and the aluminum oxalate chelate solution is added to the reaction kettle at a second flow rate, wherein the second flow rate is 0.25-0.4 mL / min; The molecular formula of the nickel manganese aluminum hydroxide precursor is Ni 1-x-y Mn x Al y (OH)2, where 0<x≤0.05, 0<y≤0.05; The nickel manganese aluminum hydroxide precursor is a microsphere structure composed of densely packed nanosheets, wherein: The volume average particle size of the microspheres is 7-15 μm; The specific surface area of ​​the microspheres is 3.0-7.5 m 2 / g; The tap density of the microspheres is 1.5-2.5 g / cm 3 ; The thickness of the nanosheet is 15-50 nm; The width of the nanosheet is 100-500 nm; The length of the nanosheet is 100-500 nm.

2. The method for preparing a nickel-manganese-aluminum hydroxide precursor according to claim 1, characterized in that: In step (1), the nickel salt is nickel sulfate hexahydrate; And / or, in step (1), the manganese salt is manganese sulfate monohydrate; And / or, in step (1), the molar ratio of the nickel salt to the manganese salt is 18:1; And / or, in step (1), the aluminum salt is aluminum sulfate; And / or, in step (1), the oxalate is sodium oxalate; And / or, in step (1), the molar ratio of the aluminum salt to the oxalate is 3:1; And / or, in step (1), the molar ratio of the aluminum salt to the manganese salt is 1:1; And / or, in step (1), the hydroxide is sodium hydroxide; And / or, in step (1), the molar ratio of the hydroxide to the manganese salt is 40:1; And / or, in step (1), the ammonium compound is aqueous ammonia; And / or, in step (1), the molar ratio of the ammonium compound to the manganese salt is 27:1 or 36:1; And / or, in step (1), the stirring speed of the coprecipitation reaction is 600 rpm or 800 rpm; And / or, in step (1), the reaction temperature of the coprecipitation reaction is 50°C or 55°C; And / or, in step (1), the protective gas is argon or nitrogen; the flow rate of the protective gas is 50 mL / min or 100 mL / min; And / or, in step (2), the aging reaction time is 10 h or 20 h.

3. The method for preparing a nickel-manganese-aluminum hydroxide precursor according to claim 2, characterized in that: The concentration of the nickel-manganese salt solution is 2 mol / L; and / or, the concentration of the aluminum oxalate chelate solution is 0.2 mol / L; and / or, the concentration of the hydroxide solution is 4 mol / L or 5 mol / L; and / or, the concentration of the ammonium compound solution is 3.6 mol / L or 4.5 mol / L; and / or, the concentration of the base solution is 0.8 mol / L or 1.2 mol / L; And / or, the stirring speed of the pretreatment is 600 rpm or 800 rpm; And / or, the reaction temperature of the pretreatment is 50°C or 55°C; And / or, the flow rate of the protective gas is 50 mL / min or 100 mL / min; and / or, during the coprecipitation reaction, the pH value in the reaction container is 11.0 or 11.2; And / or, the first flow rate is 0.5 mL / min; and the second flow rate is 0.25 mL / min.

4. The method for preparing a nickel-manganese-aluminum hydroxide precursor according to claim 1, characterized in that: The molecular formula of the nickel manganese aluminum hydroxide precursor is Ni 0.90 Mn 0.05 Al 0.05 (OH)2.

5. The method for preparing a nickel-manganese-aluminum hydroxide precursor according to claim 1, characterized in that: The volume average particle size of the microspheres is 8 μm, 10 μm, 11 μm or 13 μm; The specific surface area of ​​the microspheres is 4.5 m 2 / g or 6.2 m 2 / g; The tap density of the microspheres is 2.1 g / cm 3 ; The thickness of the nanosheet is 30 nm; The width of the nanosheet is 300 nm; The length of the nanosheet is 300 nm.

6. A nickel-manganese-aluminum oxide positive electrode material, characterized in that: The method comprises preparing a nickel manganese aluminum hydroxide precursor and a lithium salt according to the method for preparing a nickel manganese aluminum hydroxide precursor according to any one of claims 1 to 5, wherein the chemical formula of the nickel manganese aluminum oxide positive electrode material is LiNi 1-x-y Mn x AlyO2, wherein 1-xy is 0-0.8, x is 0-0.1, and y is 0-0.

1.

7. A method for preparing the nickel-manganese-aluminum oxide positive electrode material as claimed in claim 6, characterized in that: The nickel manganese aluminum hydroxide precursor is mixed with a lithium salt and sintered, wherein the sintering is a two-stage sintering.

8. The method for preparing the nickel-manganese-aluminum oxide positive electrode material according to claim 7, characterized in that: The two-stage sintering includes a first stage sintering and a second stage sintering; the heating rate of the two-stage sintering is 2-5°C / min, wherein the sintering temperature of the first stage sintering is 400-600°C, and the sintering time is 4-6 h; the sintering temperature of the second stage sintering is 700-800°C, and the sintering time is 12-18 h.

9. Use of the nickel-manganese-aluminum oxide positive electrode material as claimed in claim 6 in a lithium-ion battery.

Citation Information

Patent Citations

  • Cobalt-free lithium-rich ternary anode material NMA and preparation method thereof

    CN109686970A

  • Cobalt-free high-nickel ternary positive electrode material, preparation method thereof and method for preparing battery positive electrode

    CN113809294A

  • Spherical high-nickel cobalt-free single crystal precursor and preparation method thereof

    CN112939095A